2012
DOI: 10.1007/s00216-012-6290-2
|View full text |Cite
|
Sign up to set email alerts
|

Speciation of Np(V) uptake by Opalinus Clay using synchrotron microbeam techniques

Abstract: Synchrotron-based X-ray absorption spectroscopy has been used to determine the chemical speciation of Np sorbed on Opalinus Clay (OPA, Mont Terri, Switzerland), a natural argillaceous rock revealing a micro-scale heterogeneity. Different sorption and diffusion samples with Np(V) were prepared for spatially resolved molecular-level investigations. Thin sections of OPA contacted with Np(V) solution under aerobic and anaerobic conditions as well as a diffusion sample were analysed spatially resolved. Micro-X-ray … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…Catalano et al found out certain regions of high uranium concentration from SR‐μ‐XRF mapping of uranium distribution in contaminated sediments and collected μ‐XAF, μ‐XANES and μ‐XRD spectra at these hotspots to explore the speciation of uranium. The elemental distributions of Np, Fe and Ca were determined by Fröhlich et al using SR‐μ‐XRF mapping to work out the regions of high Np concentration. Further investigation on them via micro‐XAFS was performed to determine the oxidation state of Np.…”
Section: Synchrotron Radiation X‐ray Fluorescence (Sr‐xrf) For Elemenmentioning
confidence: 99%
“…Catalano et al found out certain regions of high uranium concentration from SR‐μ‐XRF mapping of uranium distribution in contaminated sediments and collected μ‐XAF, μ‐XANES and μ‐XRD spectra at these hotspots to explore the speciation of uranium. The elemental distributions of Np, Fe and Ca were determined by Fröhlich et al using SR‐μ‐XRF mapping to work out the regions of high Np concentration. Further investigation on them via micro‐XAFS was performed to determine the oxidation state of Np.…”
Section: Synchrotron Radiation X‐ray Fluorescence (Sr‐xrf) For Elemenmentioning
confidence: 99%
“…Although information concerning spatial heterogeneity in uptake mechanism would be essential, studies involving petrographic thin sections after sorption experiments are very limited and dealing only with other elements such as Np (e.g. Fröhlich et al 2012). Investigations with high sensitivity analytical methods such as micro-XRF are missing for BCF.…”
Section: Introductionmentioning
confidence: 99%
“…This difference was addressed to a possible reduction of Np(V) to Np(IV) within the clay. This effect has already Brought to you by | New York University Bobst Library Technical Services Authenticated Download Date | 5/31/15 2:06 PM been observed in sorption experiments under anaerobic conditions [22] and in XAFS spectroscopic investigations [31]. Taking into account the findings of the present work, the more visible differences between sorption and diffusion experiments found by Wu et al [24] may also be partly a result of differences in properties (e.g., mineralogical composition) of the OPA samples as different batches of OPA were used.…”
Section: Effect Of Ha On the Interaction Between Np(v) And Opa -Compamentioning
confidence: 82%
“…The intact OPA bore cores used in the diffusion experiments as well as the powder for batch experiments under same experimental conditions were taken from the bore core BLT 14. The elemental composition of this OPA batch has been analyzed by XRF and published in [31]. There were only slight differences in the elemental composition of BHE-24/1 and BLT 14.…”
Section: Opalinus Claymentioning
confidence: 99%